PENGARUH PIJAT BAYI TERHADAP DURASI TIDUR PADA BAYI UMUR 1-3 BULAN - Aswitami, Gusti Ayu Pramita; Udayani, Ni Putu Mirah Yunita (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
Sleep is the baby's main requirement because when the baby falls asleep growth and development will be optimal and there will be an increase in brain function and body metabolism. In infants aged 1-3 months have a sleep duration of 14 hours-18 hours per day. Baby's growth and development will be less optimal if there is a sleep disorder. Baby massage is one way to overcome the problem of sleeping in a baby. Baby massage is a gentle rubbing motion on the surface of the baby's body from face to foot. This massage will help relax the baby's muscles and facilitate blood circulation so that the baby becomes calmer and sleeps more soundly. This study aims to determine the effect of infant massage on sleep duration in infants aged 1-3 months. The design of this study used a pre-experimental design with the design of one group pretest-posttest design without a control group. Samples are infants aged 1-3 months, totaling 42 people selected by purposive sampling. The variables measured in this study were infant massage and sleep duration. This study used a statistical test paired t-test (a = 0.05). The results of this study are that there is an effect of infant massage on the duration of infant sleep, this is confirmed by the value of Wilcoxon test with sig 0,000 which then tested the hypothesis with a value of α = 0.05. With a sig value of 0,000